GOVERNMENT POLICY IN MANAGING SUGAR PRICES IN THE PANDEMIC COVID 19 - Rafiqi, Rafiqi; Saidin, OK; Lubis, M. Yamin; Ikhsan, Edy (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
In 2019 the world was hit by the health disaster Covid 19. If you look at the 37th WHO Report on the situation of the first Covid 19 in China on December 8, 2019. The food sector, a commodity that many people consume is rice, sugar, flour and soybeans. The Covid 19 impact also affected North Sumatra specifically regarding food. One of the basic needs of the people is related to sugar consumption. Sugar prices are rising and the lack of sugar supply is complained by the community. In North Sumatra. The problem in this research is how the government policy in dealing with the price of sugar during the Covid 19 pandemic and the factors of rising sugar prices. The discussion in this research is the Government to establish a policy of large-scale social restrictions (PSBB). This policy is also the situation in Government Regulation Number 21 of 2020 concerning Large-scale Social Restrictions and Presidential Decree Number 11 of 2020 Determination of the Covid Public Health Emergency 19. The occurrence of the Regional Quarantine (Lockdown) caused the phenomenon of home employees, termination of employment (PHK) and various companies start to go bankrupt. Based on data from the Ministry of Manpower (Kemnaker) in 2020, the number of workers formulated and laid off during the pandemic has reached 1,943,916 people from 114,340 companies.